2018
DOI: 10.1007/s00253-018-8856-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the sequence diversity in glycoside hydrolase family 13_18 reveals a novel glucosylglycerol phosphorylase

Abstract: In the carbohydrate-active enzyme database, GH13_18 is a family of retaining glycoside phosphorylases that act on α-glucosides. In this work, we explored the functional diversity of this family by comparing distinctive sequence motifs in different branches of its phylogenetic tree. A glycoside phosphorylase from Marinobacter adhaerens HP15 that was predicted to have a novel function was expressed and characterised. The enzyme was found to catalyse the reversible phosphorolysis of 2-O-α-D-glucosylglycerol with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Ms GGaPs, St GGaPs and Ec GGaPs, respectively) catalyse the reversible phosphorolysis of glucosylglycerate into G1P and d -glycerate. Very recently, an enzyme from Marinobacter adhaerens HP15 able to catalyse the reversible phosphorolysis of 2- O -α- d -glucosylglycerol has been characterized and named as glucosylglycerol phosphorylase ( Ma GGoP [27]).…”
mentioning
confidence: 99%
“…Ms GGaPs, St GGaPs and Ec GGaPs, respectively) catalyse the reversible phosphorolysis of glucosylglycerate into G1P and d -glycerate. Very recently, an enzyme from Marinobacter adhaerens HP15 able to catalyse the reversible phosphorolysis of 2- O -α- d -glucosylglycerol has been characterized and named as glucosylglycerol phosphorylase ( Ma GGoP [27]).…”
mentioning
confidence: 99%
“…Another novel phosphorylase specificity was discovered by searching GH13_18 for sequences that do not contain the characteristic motif of SP, SPP and GGaP in loop A. Sequences with a peculiar VGAIYQ motif were found in a clade that is interlocked between those of SPs and promiscuous SPPs (Figure 2, Figure S1). Expression and characterisation of an enzyme from Marinobacter adhaerens from this clade revealed that they are strict 2-O-glucosylglycerol phosphorylases (GGoP; EC 2.4.1.359) [18]. Glucosylglycerol is a compatible solute, just like glucosylglycerate, and GGoP is the only known enzyme that can catalyse its phosphorolysis in glucosylglycerol-producing organisms.…”
Section: -O-glucosylglycerol Phosphorylasementioning
confidence: 99%
“…Glu264 and Gln378 were predicted to be binding partners too, but their influence has yet to be verified in vitro. Finally, in the GGaP from M. silvanus and the GGoP from M. adhaerens, a few specificity-determining residues have been uncovered by molecular docking in a homology model followed by mutagenesis [15,18]. Substitution of Asn275 and Glu383 severely decreases the activity of GGaP.…”
Section: Enzymementioning
confidence: 99%
“…Similarly, glucosylglycerol phosphorylase-like sequences can be distinguished from others by the conserved VGA motif in one of the acceptor site loops (loop A; motif at positions 331-333 in the Marinobacter adhaerens enzyme). The alanine residue is predicted to participate in hydrophobic interaction with the C 1' carbon of glucosylglycerol [10]. In the neighbouring clades of sucrose and sucrose 6 F -phosporylases, that alanine is always replaced by aspartate.…”
Section: Searching the Subfamily Gh13_18 For New Functionsmentioning
confidence: 99%
“…No new specificities from evolutionarily closely related sequences were found until 2014, when Verhaeghe et al [8] described a phylogenetic neighbour that was specialised in the phosphorolysis of sucrose 6 F -phosphate (EC 2.4.1.329), albeit with a very broad substrate specificity. Rational searches for other new functions led to the recent discovery of glucosylglycerate phosphorylases (EC 2.4.1.352) [9], glucosylglycerol phosphorylases (EC 2.4.1.359) [10] and sucrose 6 F -phosphorylases with a strict substrate specificity [11,12].…”
Section: Introductionmentioning
confidence: 99%